Contemporary patterns of transatlantic trade cooperation in a post-Brexit European Union (dis)order - Iulia-Anamaria Ghidiu (CES Working Papers, 2019)
This paper aims to examine the debate surrounding negotiations of the Transatlantic Trade and Investment Partnership (TTIP). The EU and US began negotiations for this comprehensive commercial agreement in July 2013 and have still not reached consensus. This article aims to assess the possibility of resuming talks on this sensitive topic in light of the current administration in the White House, or of the European Union potentially shifting its attention to other global partners, in a period when it is visibly undergoing a number of internal crises.
Keywords: 330; transatlantic alliance; TTIP; Brexit; trade wars; emerging powers